Does Employee Engagement Mediate in the Relationship between Compensation Management and Employee Retention? - Md. Sahedur Rahman; Alam, Md. Mahbub; Taniya, Rabeya Khatun (International Journal of Scientific Research and Management (IJSRM), 2024)
Employee retention is critical to the success of any business or organization, including private universities in Bangladesh. The present study aimed to determine the mediating effect of employee engagement in the relationship between compensation management and employee retention among faculty members at private universities in Bangladesh. This study employed a cross-sectional survey method using a purposive sampling technique. The sample size was 160 PhD-holding permanent faculty members of selected private universities located in Dhaka and Chittagong, Bangladesh. Data was analysed by using SPSS version 22.0 and Smart-PLS software version 4.0.9.2. The finding of this study shows that there is a positive relationship between compensation management and employee retention, compensation and employee engagement, and employee engagement and employee retention. The results also show that employee engagement mediates the relationship between compensation management and employee retention. This study recommended that university HR professionals must prioritise competitive compensation packages and the creation of an engaging work environment. Finally, the study implications, limitations and suggestions for the future are discussed.